2021
DOI: 10.1080/17441692.2021.1981974
|View full text |Cite
|
Sign up to set email alerts
|

Agency under constraint: Adolescent accounts of pregnancy and motherhood in informal settlements in South Africa

Abstract: Progress in adolescent sexual and reproductive health (SRH) remains unequal: adolescent pregnancies are more likely to occur in marginalised communities, or in very poor households. This study aimed to comprehend from adolescents' own perspectives, the circumstances of falling pregnant and coping with motherhood in informal settlements in South Africa, to better understand the SRH challenges adolescents in these settings may face. A qualitative study was carried out over a two-month period in 2019 to analyse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…Similar findings were also reported in South Africa by Gillespie, et al (25) who explored adolescents' perspectives of falling pregnant and motherhood in informal settlements. Gillespie et al (25) found that adolescents' agency to prevent unintended pregnancies was compromised by limited adolescent-friendly SRH services and a lack of communication on SRH practices including issues of safe sex and contraception. Some adolescents reported that they were not comfortable to access SRH services in their community due to fears of being judged and limited privacy at the clinics.…”
Section: Agency and Autonomysupporting
confidence: 86%
See 3 more Smart Citations
“…Similar findings were also reported in South Africa by Gillespie, et al (25) who explored adolescents' perspectives of falling pregnant and motherhood in informal settlements. Gillespie et al (25) found that adolescents' agency to prevent unintended pregnancies was compromised by limited adolescent-friendly SRH services and a lack of communication on SRH practices including issues of safe sex and contraception. Some adolescents reported that they were not comfortable to access SRH services in their community due to fears of being judged and limited privacy at the clinics.…”
Section: Agency and Autonomysupporting
confidence: 86%
“…Agency and autonomy were also linked to uptake of SRH services. Limited access to adolescent friendly SRH services restricted girls' agency to prevent unintended pregnancies (27) or to take up SRH support (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aspects of the interview guides focusing on the causes of adolescent pregnancy, the impact of motherhood, and the gender roles involved, pertaining to interviews with young men and women residing in the informal settlements, were reported in a separate but related paper ( Gillespie et al, 2021 ) and therefore not repeated here.…”
Section: Methodsmentioning
confidence: 99%